Establishment of syngeneic murine model for oral cancer therapy - Chen, Yi-Fen; Chang, Kuo-Wei; Yang, I-Ting; Tu, Hsi-Feng; Lin, Shu-Chun (Oral oncology, 2019)
•Establishment of two murine cell lines from tongue SCC by 4NQO induction.•MTCQ1 can induce primary tumors, regional metastasis and distal metastasis.•Inhibition of oncomiRs reduced MTCQ1-GFP oncogenicity.•CDDP and PD-L1 blockage abrogate the MTCQ1 tumor growth in vivo. Oral carcinoma (OSCC) is one of the most important causes of cancer death worldwide. OSCC cell lines and preclinical rodent models are crucial to addressing the mechanisms of OSCC and helping the development of new therapeutic strategies and interventions. The establishment of murine OSCC cell lines and syngeneic models are necessary to allow concordant investigation of both in vitro and in vivo pathogenesis. In this study, we established two murine tongue squamous cell carcinoma cell lines, designated MTCQ1 and MTCQ2, from 4NQO-induced OSCC using C57BL/6 mice. These cell lines express a variety of epithelial markers but produce only a tiny amount of E-cadherin. The expression of mesenchymal and stemness regulators are evident, and this is associated with the high mobility in these cell lines. MTCQ1 also shows high Ki67 and PCNA expression, and complicated alterations in p53 expression, which may underlie its high clonogenic potential and rapid orthotopic tumor induction. Using the MTCQ1 cell subclone tagged with GFP (MTCQ1-GFP), extensive neck nodal metastasis and lung metastasis were identified by immunostaining and fluorescence imaging. Inhibition of oncogenic miRNAs, particularly miR-134, was able to attenuate the oncogenicity of MTCQ1-GFP. Cisplatin treatment inhibited both in vitro and in vivo growth of MTCQ1-GFP, and it was found to decrease miR-134 expression in this subclone. The anti-PD-L1 treatment enhanced the inhibitory effects of cisplatin against tumorigenesis. This syngeneic preclinical model should help provide valuable mechanistic insights into OSCC, as well as helping with the development of new approaches to treating this disease.